Selective nitrogen functionalization of graphene by bucherer-type reaction - Chua, Chun Kiang (2015)
Nitrogen functionalization of graphene offers new hybrid materials with improved performance for important technological applications. Despite studies highlighting the dependence of the performance of nitrogen-functionalized graphene on the types of nitrogen functional groups that are present, precise synthetic control over their ratio is challenging. Herein, the synthesis of nitrogen-functionalized graphene rich in amino groups by a Bucherer-type reaction under hydrothermal conditions is reported. The efficiency of the synthetic method under two hydrothermal conditions was examined for graphite oxide produced by Hummers and Hofmann oxidation routes. The morphological and structural properties of the amino-functionalized graphene were fully characterized. The use of a synthetic method with a well-known mechanism for derivatization of graphene will open new avenues for highly reproducible functionalization of graphene materials.